Regional cultural policy of the Caribbean Community Member States (CCS GeorgetownGY, 1994)
Seeks to provide an overall rationale of the significance of culture in development, and some guidelines for Member States in the formation or adaptation of their national policies. Tries to help ensure to some degree, unity of outlook at the regional level on the role of culture in the development process, and to indicate some areas which should be targeted for specific action within certain time-frames.
Keywords: CULTURAL POLICY